2011
DOI: 10.1590/s0034-737x2011000500020
|View full text |Cite
|
Sign up to set email alerts
|

Produção vegetal e de óleo essencial de boldo pequeno em função de fontes de adubos orgânicos

Abstract: Effect of organic fertilizer sources on biomass and essential oil production of Plectranthus neochilus SchlechterApplication of organic fertilizers to medicinal aromatic plants usually has a positive effect on biomass and essential oil production. Plectranthus neochilus Schlechter was cultivated with three organic fertilizer sources. This study evaluated the biomass production and content, yield and chemical composition of the essential oil. The seedlings, after acclimatization, were transplanted to 10L pots a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
3
8
0
14
Order By: Relevance
“…Studies by Scheffer et al (1993) showed a positive response of A. millefolium to organic fertilization, confirming the results observed in the present study. Other studies, which have evaluated the increase in biomass production in medicinal and aromatic plants by the application of organic fertilizers, showed similar results (BRANT et al, 2010;CORRÊA et al, 2010;COSTA et al, 2008;ROSAL et al, 2011). Analysing the RDW, a quadratic response was seen, where the point of maximum accumulation was 35 g plant -1 at a dosage of 6 kg m -² for poultry manure and 28 g plant -1 at a dosage of 12 kg m -² for cattle manure (Figures 2 C and D).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Studies by Scheffer et al (1993) showed a positive response of A. millefolium to organic fertilization, confirming the results observed in the present study. Other studies, which have evaluated the increase in biomass production in medicinal and aromatic plants by the application of organic fertilizers, showed similar results (BRANT et al, 2010;CORRÊA et al, 2010;COSTA et al, 2008;ROSAL et al, 2011). Analysing the RDW, a quadratic response was seen, where the point of maximum accumulation was 35 g plant -1 at a dosage of 6 kg m -² for poultry manure and 28 g plant -1 at a dosage of 12 kg m -² for cattle manure (Figures 2 C and D).…”
Section: Resultssupporting
confidence: 57%
“…Several aromatic species have been studied in order to assess the effects of organic fertilization on plant productivity and the synthesis of their volatile constituents, such as Plectranthus neochilus Schltr. (ROSAL et al, 2011), Aloysia triphylla Britton. (BRANT et al, 2010, Origanum vulgare L. (CORRÊA et al, 2010), Ocimum gratissimum L. (BIASI et al, 2009), Salvia fruticosa Mill.…”
Section: Introductionmentioning
confidence: 99%
“…Então a sua produção é, em geral, resposta ao estresse. Rosal et al (2011) destacam que não se possui na literatura um consenso sobre o rendimento do óleo essencial, em relação ao tipo de adubação e muito menos das dosagens recomendadas. Isso pode estar relacionado ao fato de as plantas medicinais serem muito diversificadas, e com grande variabilidade na produção de metabólitos secundários.…”
Section: Resultsunclassified
“…O metabolismo primário e secundário é afetado por diversos fatores externos, sendo a disponibilidade de nutrientes um desses fatores (BIASI et al, 2009). Segundo Rosal et al (2011), devemos considerar as possíveis variações quantitativas e qualitativas que podem ocorrer na biossíntese dos metabólitos secundários, em resposta à aplicação de técnicas agronômicas.…”
Section: Introductionunclassified
“…Alguns autores encontraram interferência desses materiais orgânicos na produção de compostos secundários e nos teores de clorofila das plantas, como Berilli et al (2016) e Quartezani et al (2018 nos índices de flavonóides de mudas de café com a aplicação de lodo de curtume, Rosal et al (2011) nos teores de óleos essenciais da espécie Plectranthus neochilus Schltr, aplicando esterco de aves e Amorim (2014) no acúmulo de clorofilas a e b da espécie Plectranthus amboinicus (Lour.) com esterco bovino e cama de frango.…”
Section: Introductionunclassified